Sperm Agglutination in Infertile Men and The Success Rate of Intrauterine Insemination in Rumah Sakit Ibu dan Anak Puri Bunda Denpasar - Anak Agung Sintya Padma Dewi; I Gusti Ngurah Pramesemara; Yukhi Kurniawan; I Gusti Ayu Widianti (Indonesian Andrology and Biomedical Journal, 2023)
Background: Every human being, especially a married couple, wants children. Obstacles to obtaining children are called infertility. One of the Assisted Reproductive Technology (ART) procedures used for treating infertility is intrauterine insemination (IUI), a non-invasive procedure with affordable costs. The success of IUI is influenced by many factors, one of which is sperm agglutination. Objective: This study determined the relationship between sperm agglutination and the success rate of the IUI procedure. Methods: The study is a descriptive-analytic study with a cross-sectional approach. The sample collection technique uses non-probability. The data used were medical records of male patients diagnosed with infertility, aged 25-45 years, and undergoing IUI procedures at the Rumah Sakit Ibu dan Anak Puri Bunda Denpasar from January to July 2022. Results: Of the 91 samples obtained, 9 people experienced sperm agglutination (9,9%), and 82 people did not experience sperm agglutination (90,1%). The success rate of the IUI procedure was 29 people (31,9%), 1 person (11.1%) experiencing sperm agglutination, and 28 people (34,1%) not experiencing sperm agglutination. Fisher's Exact test carried out has obtained a result (p=0.263). And the value of the odds ratio (OR) obtained=0.241) Conclusion: This study concluded that there is no significant relationship between sperm agglutination in infertile men and the success rate of the IUI procedure. The value of OR showed sperm agglutination is not included in the factors that affect the success rate of IUI. Keywords: Sperm Agglutination, Intrauterine Insemination, Male Infertility